Wikidata and DBpedia: A journey to the center of a web of data - Saorín, Tomás; Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2018)
DBpedia y Wikidata are two semantic projects built on the top of Wikipedia encyclopedic content that has been crowdsourced, created, and maintained by thriving online communities. This article outlines differences and similarities between these two projects, pointing out their data models, curation patterns, and technologies. In addition, it forecasts some possible trends for their co-evolution as crossdomain open knowledge graphs and their significant value as hubs of interlinking datasets of various domains.
Keywords: Wikidata; DBPedia; Semantic web; Ontologies; Open Knowledge graph.